Application of 2.4 GHz Frequency Band Anti-Interference Performance Improvement and Transformation Based on CBTC Vehicle-Ground Wireless Communication System - ZHAN Lihui; CHEN Shuhua; WANG Lei (Chengshi guidao jiaotong yanjiu)
［Objective］Urban rail transit uses a 2.4 GHz frequency band vehicle-ground wireless communication system for the signal system, which is extremely susceptible to interference from communication operators, civilian WiFi, personal hotspots, Bluetooth, RFID (radio frequency identification) technology and other equipment, resulting in frequent vehicle-ground communication interruptions and even affecting the normal operation of trains. Therefore, it is necessary to study the anti-interference performance and application transformation measures of the 2.4 GHz frequency band in CBTC (communication-based train control) vehicle-ground wireless communication system. ［Method］The problem of train emergency braking failure caused by vehicle-ground communication interruption, as well as the solution to improve anti-interference performance are introduced; taking a certain metro line in Hangzhou as example, a 5.8 GHz frequency band transformation project is carried out through on-site testing and other methods. ［Result & Conclusion］The anti-interference performance is improved by taking various measures such as investigating and rectifying fixed interference sources, installing shielding devices, and adjusting the frequency bands of communication operators. Based on current situations of the 5.8 GHz frequency band application and channel occupancy in the line network, the vehicle-ground wireless networking mode is transformed from 2.4 GHz (A network)+2.4 GHz (B network) to 2.4 GHz (A network)+5.8 GHz (B network). After taking a variety of anti-interference measures, vehicle-ground communication failures are alleviated. Through the transformation and application of the 5.8 GHz frequency band, the train emergency braking problem caused by vehicle-ground wireless communication interruption on a certain line of Hangzhou Metro is solved.